(untitled) (Eurasian Research Bulletin, 2023)
The study of the concept "kinship" is the focus of this article. This article explores numerous methods for studying kinship words in the Uzbek and English languages, as well as their classification and selection criteria. Kinship determines social relationships, establishes a person’s status in society, and modifies his conduct. The terminology kinship attributes also reflection of the uniqueness of the language, the particulars of the national course, and, as a result, define the national mindset